Kinematic and biodynamic model of the long jump technique - Coh, M.; Žvan, M.; Kugovnik, O. (Kinematics, 2017)
The main aim of the study was to determine the kinematic model for long jump and define the kinematic and dynamic parameters of an elite long jumper`s technique. The theoretical model was based on real data where the jumper was defined with a joint mass point. In view of certain previous similar studies, our study identified kinematic and dynamic parameters directly without using the inverse mechanics method. The analysis was made on two jumps of the top level athlete G.C., who won the bronze medallion in long jump at the World Championships in Seville. The kinematic parameters of the take-off, flight and landing were measured with a 3-D video ARIEL system (Ariel Dynamics Inc., USA). The dynamic characteristics of take-off in the X, Y and Z axes were registered with a force-platform (KISTLER-9287), which was installed immediately prior the take-off board. The take-off efficiency was defined best by the following parameters: horizontal velocity, VXTO—8.10 m s-1; vertical velocity, VYTO—3.90 m s-1; angle of projection, PATO—24.1°; duration of compression phase, TDMKF—84 ms, duration of lift phase, MKFTO—43 ms and maximal force in Y-vertical axis, FYMAX—5132 N. An important factor of a rational technique of long jump is also the landing, which is defined by the landing distance and fall-back distance. The efficiency of the landing depended on the landing distance L3—0.63 m and fall-back distance LFB, which amounted to 0.15 m.